Effect of Thermocapillary Flow on the Surface Profile in Pulsed Laser Micro Polishing - Ma, Chao; Vadali, Madhu; Duffie, Neil A.; Pfefferkorn, Frank E.; Li, Xiaochun (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
The objective of this paper is to understand and predict how surface profiles produced by thermocapillary flow change with material properties and process parameters during pulsed laser micro polishing. Thermocapillary flow is driven by surface tension gradient which is induced by temperature gradient in a melt pool. Experimental work has shown that great reductions in surface roughness can be achieved by manipulating thermocapillary flow (thermocapillary regime). The existing surface prediction model only works for pulsed laser micro polishing through damping of stationary capillary waves (capillary regime) where thermocapillary flow is negligible. It is desirable to develop a predictive capability for the thermocapillary regime to offer guidance for parameter selection and optimization. Analytical heat transfer and fluid flow models are derived for laser induced thermocapillary flow. A dimensionless number, normalized average displacement (NAD) of a liquid particle during thermocapillary flow, is proposed and calculated directly from material properties and laser process parameters. NAD is found to be strongly correlated with the surface profile introduced by thermocapillary flow and successfully used to predict polishing achievable in thermocapillary regime. Combining this model with the existing surface prediction model will enable prediction over a wide range of parameters.
Keywords: Polishing; Micro; Modeling; Pulse Laser; Laser; Marangoni Flow